Tanggung Jawab Hukum Developer atas Pengembalian Down Payment Pembelian Rumah kepada Pembeli karena Pembangunan yang Tidak Selesai - Nadila Tzusiah Dzahrah; Frency Siska (UNISBA Press, 2023)
Abstract. Down payment is a sign of the purchase of a house made by the buyer. After the down payment is paid, the developer's obligation arises to fulfill its obligations as well as the buyer's right, namely to realize the house in accordance with the agreed time. But in practice, there are still developers who commit acts of default. One of the types of default committed is a delay in construction, so the buyer has the right to demand accountability for acts of negligence committed by the developer by asking to return the down payment that has been paid in accordance with the Civil Code and Regulations in the Field of Housing and Residential Areas. This study aims to understand the responsibility of developers for returning down payments due to incomplete construction and to understand the application of developer responsibility for losses to home buyers due to down payments that have been paid to developers who do not complete house construction in terms of Book III of the Civil Code and Regulations in the Field of Housing and Residential Areas. The approach method used in this research is normative juridical by using analytical descriptive research specifications. The data collection technique used is library research using secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials and the analytical method used is qualitative juridical. The results of this study show that the developer of PT. X has defaulted, namely the delay in the construction of the house and must be held responsible for the consequences of his actions, namely returning the down payment must be in accordance with the rules contained in the Civil Code and Regulations in the Housing and Residential Areas Sector. Abstrak. Down payment merupakan suatu tanda jadi pembelian rumah yang dilakukan oleh pembeli. Setelah dibayarnya down payment maka timbulah kewajiban developer untuk memenuhi kewajibannya sekaligus hak bagi pembeli yakni merealisasikan rumah sesuai dengan waktu yang sudah diperjanjikan. Tetapi dalam praktiknya, masih ada developer yang melakukan tindakan wanprestasi. Salah sagtu jenis wanprestasi yang dilakukan adalah keterlambatan pembangunan, maka pembeli berhak untuk meminta pertanggungjawaban atas tindakan kelalaian yang dilakukan pihak developer dengan meminta mengembalikan down payment yang telah dibayarkan sesuai dengan KUHPerdata dan Peraturan di Bidang Perumahan dan Kawasan Pemukiman. Penelitian ini bertujuan untuk memahami tanggung jawab developer atas pengembalian down payment karena pembangunan yang tidak selesai dan untuk memahami penerapan tanggung jawab developer atas kerugian pembeli rumah akibat down payment yang sudah dibayarkan kepada developer yang tidak menyelesaikan pembangunan rumah ditinjau dari Buku III KUHPerdata dan Peraturan di Bidang Perumahan dan Kawasan Pemukiman. Metode pendekatan yang digunakan dalam penelitian ialah yuridis normatif dengan menggunakan spesifikasi penelitian deskriptif analitis. Teknik penggumpulan data yang digunakan yaitu studi kepustakaan dengan menggunakan data-data sekunder yang terdiri dari bahan hukum primer, bahan hukum sekunder, serta bahan hukum tersier dan metode analisis yang digunakan ialah yuridis kualitatif. Hasil dari penelitian ini memperlihatkan bahwa developer PT. X telah melakukan wanprestasi yaitu keterlambatan pembangunan rumah dan harus bertanggungjawab akibat dari tindakannya yakni mengembalikan down payment sesuai dengan aturan yang tercantum dalam KUHPerdata dan Peraturan di Bidang Perumahan dan Kawasan Pemukiman.